Electrospun extracellular matrix scaffold improves cardiac structure and function post‐myocardial infarction. (1st July 2022) - Hayam, Rotem; Ertracht, Offir; Zahran, Sharbel; Baruch, Limor; Atar, Shaul; Machluf, Marcelle
Abstract: The current unmet clinical need for post‐myocardial infarction (MI) treatments has driven the development of diverse scaffolds for regenerating the infarcted area, based on natural and synthetic polymers. Decellularized porcine cardiac extracellular matrix (pcECM) has emerged as a promising biomaterial for cardiac regeneration, due to its unique bioactivity and microstructure that mimic the natural tissue. We have previously reported the development of an electrospun pcECM cardiac scaffold that was shown to preserve the mechanical, structural, and biological properties of cardiac ECM while allowing a controllable reproducible production. In the present work, however, we reveal the potential of this unique scaffold as a possible treatment post‐MI. Two types of electrospun pcECM scaffolds, varying in thickness, were applied to rat hearts, 4 weeks following MI induction, thus allowing cardiac deterioration and a scar tissue formation before treatment (chronic model). Our results show moderated remodeling, decreased scar, and reduced wall thinning accompanied by a partial functional recovery in the hearts of both treatment groups when compared to the control. When examining the different structural and functional parameters of the heart, however, the advantage of the thicker electrospun pcECM scaffold is revealed. Hence, significant improvement was obtained in important structural parameters such as wall thickness and functional parameters such as ejection fraction. Altogether, our results indicate the potential applicability of electrospun pcECM scaffolds for cardiac regeneration, establishing the basis for advanced preclinical research using large animal models.